1985
DOI: 10.1002/eji.1830151217
|View full text |Cite
|
Sign up to set email alerts
|

T cells specific for different antigens express different HLA‐D region products

Abstract: T cell lines and clones were analyzed for surface expression of Ia antigens using monoclonal antibodies (mAb) that detect monomorphic and polymorphic epitopes on Ia molecules encoded by the HLA-DR and HLA-DQ gene clusters. All mAb bound to B lymphocytes or lymphoblastoid cell lines of the same individuals from whom the T cells were derived. Three mAb detecting monomorphic epitopes, primarily associated with HLA-DR, bound to all T cells showing that each clone or line expressed some type of Ia. Three other mAb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The differential binding patterns of these antibodies might occur because the epitopes recognized can be present in a different Ia antigen setting, precedents of which have been reported for activated T cells (35) and for the epitope detected by reagent 109d6 in patients with RA (36). A similar differential expression of Ia antigens with similar kinetics and dose-response curves has also been found with dermal fibroblasts (14) or synovial fibroblast cell lines after incubation with y-IFN (ref.…”
Section: Discussionmentioning
confidence: 95%
“…The differential binding patterns of these antibodies might occur because the epitopes recognized can be present in a different Ia antigen setting, precedents of which have been reported for activated T cells (35) and for the epitope detected by reagent 109d6 in patients with RA (36). A similar differential expression of Ia antigens with similar kinetics and dose-response curves has also been found with dermal fibroblasts (14) or synovial fibroblast cell lines after incubation with y-IFN (ref.…”
Section: Discussionmentioning
confidence: 95%
“…1978;Ko et at.. 1979;Engleman ct al., 1980;Zier. 1982;Schendel & Johnson, 1985;Triebel ct at., 1986). Previously, we have reported that 20-50'!^, of T cells expressed class II on the cell .surface as early as 0-5-2 h after stimulation with PHA and PdB.…”
Section: Discussionmentioning
confidence: 99%
“…HLA-DR and D typing, 2-dimensional (2-D) gel electrophoretic analysis, peptide mapping and partial aminoacid sequence have detected no difference in the phenotype and in the structural profile of HLA Class I1 antigens synthesized by activated T cells and by autologous B cells (for review, see Solheim et al 1986). Like other types of cells (Natali et al 1986), activated T cells express a higher level of HLA-DR than of HLA-DQ antigens (Schendel & Johnson 1985, Santoli et al 1986, Triebel et al 1986). Furthermore, T cell clones may differ from autologous B lymphoid cells in their reactivity pattern with monoclonal antibodies to polymorphic determinants of HLA-DR antigens (Schendel et al 1984, Santoli et al 1986, Triebel et al 1986).…”
mentioning
confidence: 99%